2000
DOI: 10.1038/sj.ijir.3900551
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sildenafil on human sperm motion and function from normal and infertile men

Abstract: The aim of this report was to study the effect of sildena®l, a speci®c type-5 phosphodiesterase inhibitor, on human sperm motility, viability, membrane integrity and sperm penetration assay.Spermatozoa were obtained from normal donors (n 6) and infertile men (n 6) were washed using a single Percoll (80%) gradient, suspended in Ham's F-10 medium, and incubated with various doses of sildena®l (125, 250 and 750 ngaml); pentoxifylline (3 mM) was used as a positive control, and Ham's F-10 was used as a reagent cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 15 publications
2
33
0
10
Order By: Relevance
“…cGMP is thought to modulate also sperm motility. Indeed, the cGMP-dependent phosphodiesterase (PDE) inhibitor sildenafil was reported by some authors (Lefievre et al 2000, Cuadra et al 2000, but not by others (Andrade et al 2000, Aversa et al 2000, Burger et al 2000, to increase the velocity and amplitude of lateral head displacement in human spermatozoa. Lefievre et al (2000) observed an inhibition of sperm PDE activity with sildenafil at high concentrations, inhibiting many PDE and causing also an increase in cAMP, whereas Cuadra et al (2000) reported that sildenafil stimulates sperm motility at much lower concentrations, quite close to the IC 50 of sildenafil for the cGMP-dependent PDE.…”
Section: Introductionmentioning
confidence: 99%
“…cGMP is thought to modulate also sperm motility. Indeed, the cGMP-dependent phosphodiesterase (PDE) inhibitor sildenafil was reported by some authors (Lefievre et al 2000, Cuadra et al 2000, but not by others (Andrade et al 2000, Aversa et al 2000, Burger et al 2000, to increase the velocity and amplitude of lateral head displacement in human spermatozoa. Lefievre et al (2000) observed an inhibition of sperm PDE activity with sildenafil at high concentrations, inhibiting many PDE and causing also an increase in cAMP, whereas Cuadra et al (2000) reported that sildenafil stimulates sperm motility at much lower concentrations, quite close to the IC 50 of sildenafil for the cGMP-dependent PDE.…”
Section: Introductionmentioning
confidence: 99%
“…Cuadra et al 45 showed that when incubated in different concentrations of sildenafil (0-40 nmol l À1 ), sperm progressive motility and hyperactivation were stimulated to a greater extent than in controls at 4 h, followed by a decrease with a dose-dependent effect. A study by Glenn et al 46 on 57 male patients showed that the number and velocity of progressively motile sperms were significantly increased between 15-135 min when incubated with sildenafil (0.67 mmol) at 37 1C for 3 h. Burger et al 47 demonstrated that sildenafil incubation (125, 250 and 750 ng ml À1 ) did not affect sperm motility and viability of washed human spermatozoa compared with Ham's control, whereas pentoxifylline (3 mM) incubation enhanced both significantly.…”
Section: In Vitro Effectmentioning
confidence: 99%
“…On normal donors and infertile men, Burger et al 47 showed that spermatozoa incubated with sildenafil and pentoxifylline demonstrated nonsignificant change in sperm penetration assay from controls. du Plessis et al 27 demonstrated that oral 50 mg sildenafil and 8-bromo-cGMP treatments on semen collected after 1 h increased sperm-zona-pellucidabinding results concluding that it can be used to enhance sperm binding to the oocyte.…”
Section: Sperm Penetration Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Burger et al, (2000) in an ex vivo study investigated the effect of sildenafil on the motility and viability of human spermatozoa. The above spermatozoal parameters were evaluated in sperm samples of both healthy donors (n=6) and clinically infertile men (n=6).…”
Section: The Development Of In Vitro Studiesmentioning
confidence: 99%